2020
DOI: 10.1097/md.0000000000020965
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with post-traumatic stress disorder of nurses exposed to corona virus disease 2019 in China

Abstract: Quantitative studies using validated questionnaires on post-traumatic stress disorder (PTSD) of Nurses exposed to corona virus disease 2019 in China are rare and the baseline PTSD must first be evaluated before prevention. This study aimed to investigate the factors potentially involved in the level of PTSD of Nurses exposed to COVID-19 in China.In this cross-sectional study, male and female Nurses (n = 202) exposed to COVID-19 from HuBei China were included in the final sample. The PTSD Checklist-Civilian (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
82
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(101 citation statements)
references
References 36 publications
11
82
1
3
Order By: Relevance
“…During the COVID-19 pandemic, several studies are being performed on the incidence of PTSD [7][8][9][10]. In April 2020, Fekih-Romdhane et al [7] investigated the presence of PTSD in 603 Tunisian people and reported that 33% of the participants had PTSD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the COVID-19 pandemic, several studies are being performed on the incidence of PTSD [7][8][9][10]. In April 2020, Fekih-Romdhane et al [7] investigated the presence of PTSD in 603 Tunisian people and reported that 33% of the participants had PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…Forte et al [8] investigated the presence of PTSD in 2,286 Italians during the massive COVID-19 outbreak in Italy and found that PTSD was present in 29.5% of the participants. Lastly, Wang et al [10] evaluated 202 nurses exposed to COVID-19 in Hubei, China, and reported that 16.8% of them had PTSD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study conducted in China that included 202 nurses exposed to COVID-19, the incidence of post-traumatic stress disorder was 16.8%. 9 Post-traumatic stress symptoms were associated with female gender, lower job satisfaction and stress coping strategies (positive relationship with negative coping strategies, inverse relationship with positive coping strategies). As yet, we still do not know the effectiveness of the psychological support measures for professionals in reducing the risk of mental pathology and post-traumatic stress disorder in health professionals.…”
mentioning
confidence: 94%
“…No obstante, el soporte psicológico individual y en grupo para estos profesionales puede ser de ayuda para reducir el malestar emocional y el estrés que sufren. En un estudio reciente realizado en China que incluyó a 202 enfermeras expuestas a la COVID-19, las tasas de estrés postraumático fueron del 16,8% 9 . Los síntomas de estrés postraumático se asociaron al género femenino, a menor satisfacción laboral y a estrategias de afrontamiento del estrés (relación positiva con estrategias de afrontamiento negativas, relación inversa con estrategias de afrontamiento positivas).…”
unclassified